Enacting the corporation : an American mining firm in post-authoritarian Indonesia - Welker, Marina, 1973- (University of California Press, 2014)
"What are corporations, and to whom are they responsible? Anthropologist Marina Welker draws on two years of research at Newmont Mining Corporation's Denver headquarters and its Batu Hijau copper and gold mine in Sumbawa, Indonesia, to address these questions. She shows how, against the backdrop of an emerging Corporate Social Responsibility movement and changing state dynamics in Indonesia, people enact the mining corporation in multiple ways: as an ore producer, employer, patron, promoter of sustainable development, religious sponsor, auditable organization, foreign imperialist, and environmental threat. Rather than assuming that corporations are monolithic, profit-maximizing subjects, Welker turns to anthropological theories of personhood to develop an analytic model of the corporation as an unstable collective subject with multiple authors, boundaries, and interests. Enacting the Corporation demonstrates that corporations are constituted through continuous struggles over relations with--and responsibilities to--local communities, workers, activists, governments, contractors, and shareholders"--